Deligne-Beilinson Cohomology and Abelian Link Invariants - Guadagnini, E.; Thuillier, F. (Symmetry, Integrability and Geometry: Methods and Applications, 2008)
For the Abelian Chern-Simons field theory, we consider the quantum functional integration over the Deligne-Beilinson cohomology classes and we derive the main properties of the observables in a generic closed orientable 3-manifold. We present an explicit path-integral non-perturbative computation of the Chern-Simons link invariants in the case of the torsion-free 3-manifolds S³, S¹ × S² and S¹ × Σg.